GCSB-5 regulates inflammatory arthritis and pain by modulating the mitogen-activated protein kinase signaling pathway in a murine model of rheumatoid arthritis - Jihye Bang; Gyeonghwa Kim; Soo Young Park; Hye Ra Jung; Sang-Hyon Kim; Ji-Min Kim (Archives of Rheumatology, 2023)
Objectives: This study aimed to determine whether GCSB-5 has anti-inflammatory and antinociceptive effects in mice with collagen-induced arthritis (CIA), an animal model of rheumatoid arthritis (RA), and investigate the influence of GCSB-5 on the mitogen-activated protein kinase (MAPK) pathway. Materials and methods: The experimental animal study was designed to include five groups: CIA mice treated with GCSB-5 (300 mg/kg), GCSB-5 (600 mg/kg), celecoxib (60 mg/kg), or saline for four weeks, and nontreated control mice. The clinical severity of arthritis was scored. Nociceptive thresholds were measured by using a von Frey dynamic plantar analgesimeter. The MAPK pathway was evaluated in mouse synovium. The expression of channels associated with pain signaling was assessed by western blot and immunohistochemical staining. Results: GCSB-5 treatment diminished the severity of clinical arthritis and increased the nociceptive threshold in mice with CIA. Celecoxib, a positive control drug, also showed comparable changes. Clinical arthritis scores were inversely related to mechanical thresholds. GCSB-5 administration decreased the levels of anti-type II collagen antibody and inflammatory cytokines in the sera of mice with CIA. Furthermore, ERK, p38 MAPK, and JNK phosphorylation were downregulated and TRPV1 and ASIC3 expression were decreased in the synovium of GCSB-5-treated mice compared to salinetreated mice. Interleukin-6-induced TRPV1 and ASIC3 upregulation were also inhibited by GCSB-5 in human RA fibroblast-like synoviocytes in vitro. Conclusion: GCSB-5 decreased inflammatory arthritis and pain in a murine model of RA. The results present evidence that GCSB-5 may be beneficial for relieving pain as well as decreasing inflammation in autoimmune arthritis, such as RA.